“Tá certo, professora Helena!”: reflexões sobre socialização em uma pré-escola em João Pessoa - Oliveira, Thays Felipe David de (2014)
In February 2013 I went to school Sonho Code to do a field research with their students. Thus, the pre-school receives students who are aged between 3 and 6 years. The school is located in João Pessoa largest neighborhood and stands out for its differentiated services to the region, such as judo school, ballet, English and religion. At first I was only with the intention to understand the socialization process that occurred between them, but I can say that already had left preconceived ideas, unfortunately not followed what Malinoswki had said in his work. However, continue the survey the children began to show me that your world was not just what I felt or thought. That is, something simple and that was limited only to play. I will start from the assumption that the child is a being active, and has the role to recreate, share and reinvent everything that is around you, in terms of Corsaro (2011) it will always make an interpretative reproduction of all that is your return. I was pleased to hear their opinions on various subjects, such as dating, friendship and even about death. Anyway, I try to show here the dialogue between anthropology and education, with an emphasis on some issues such as: how "Aunt Bia" was seen by the students, the role of school Dream Sweet in the lives of children, like to be a researcher in pre -school, and especially, what I did for the children did not feel that I was more of an adult who is there to control it. Even because, during the 6 months I spent there always questioned what I was doing adult at school playing and talking with them. In short, I want to discuss about some of the pitfalls that have arisen in continue the research in the aforementioned school.